Determinación de los contaminantes producto de la combustión en el parque automotor a diésel, en el cantón pujilí, periodo 2017-2018. - Alcocer Quishpi, Edith Patricia (2018)
The purpose of this project was to determine the possible air pollution caused by the incomplete combustion of vehicles with diesel engines at Pujilí Canton, by measuring the percentage of opacity. In this canton, it is estimated that there are 1618 diesel engine vehicles, for that reason 150 vehicles were monitored and five points were selected for the respective monitoring: The Public Mobility Company of the Commonwealth of Cotopaxi, Pujilí Integrated Stop, "El Rancho "Garage of vehicles of the GAD Pujilí, Office of the Cooperative La Merced, Syndicate of professional drivers of Pujilí. For the Opacity monitoring, the AVL DITEST gas 1000 equipment with diesel accessory DISMOKE 480 BT Opacimeter was used, applying the free acceleration method as indicated by the Ecuadorian Technical Standard NTE INEN 2 202-2000. The opacity monitoring results indicate that 67% of monitored vehicles exceed the maximum permissible limits (LPM) of emissions opacity for mobile sources with diesel engines, it means that more than half DO NOT COMPLY with the Ecuadorian Technical Standard INEN 2 207: 2002, generating a deterioration in air quality. The results obtained are a fundamental tool for the Municipality of Pujilí, Ministry of the Environment, National Traffic Agency and the Public Mobility Company of the Commonwealth of Cotopaxi, to plan pollution control and mitigation strategies emitted by mobile sources to diesel, improving air quality and the quality of life of the population at Pujilí Canton.